Study the Impact of Quality Management System ISO 9001on Machinery Breakdowns - Zahra, Ameen Ali; Osman, Jamil Chikh; Baker, Hussein (Al-Nahrain Journal for Engineering Sciences, 2018)
This research focuses on studying the importance of quality management system ISO 9001: 2015 and its impact on machinery breakdowns in the general company for the manufacture of wool and carpets in Hama for reducing the machines stops and thus increasing production quantities in the company. We did a field study in the company which a random sample of workers was interviewed in, taking into consideration the characteristics of the categories of workers.We analyzedthe dataobtainedfromthe workersby usingstatistical analysis program (SPSS19).The statistical results have shown that there is a strong correlation between the quality management system ISO 9001: 2015 and machinery breakdowns, which necessitates giving greater attention to the ISO 9001standard by the company's management and seeking ISO 9001 certification to achieve high performance for the company under study.